Ion mobility spectrometry as a fast screening tool for synthetic cannabinoids to uncover drug trafficking in jail via herbal mixtures, paper, food, and cosmetics. Issue 6 (6th February 2019) - Metternich, Sonja; Zörntlein, Siegfried; Schönberger, Torsten; Huhn, Carolin
Abstract: The greatest challenge for European drug policies is how to effectively respond to the dynamic and constantly changing market for new psychoactive substances (NPS). Even small modifications in the chemical structure of substances often allow circumventing existing laws. Also in prison, the consumption of NPS is rising and there is growing evidence that NPS are responsible for a large share of drug‐related problems. Ion mobility spectrometry (IMS) is the technique of choice for trace analysis of illicit drugs or explosives at security points, for example airports. Currently, databases of the reduced mobility (K0 ) values are limited to classical drugs and should be completed with data of emerging NPS. In this article, K0 values, LODs (0.7–3.6 ng) and drift times of 25 synthetic cannabinoids were evaluated. The data were added to existing databases of IMS which were then applied for fast screening in prison. The detection capability of the portable IMS technique was evaluated by the determination of intra‐day (0.089%) and inter‐day precision (0.004% to 0.14%), systematic error (0.19%), and separation capability for structurally related NPS. The applicability of the methodology was demonstrated by the successful analysis of 12 different pieces of paper impregnated with synthetic cannabinoids, 7 different cosmetics, and 5 food samples (liquids), spiked with a mixture of narcotic drugs and a synthetic cannabinoid. In addition, 14 herbal mixtures and 36 different casework samples from prisons were analyzed provided by the State Office of Criminal Investigation Rhineland‐Palatinate (Germany). Abstract : Ion mobility spectrometry (IMS) is the technique of choice for trace analysis of illicit drugs or explosives at security points. Currently, databases of the reduced mobility (K0 ) values are limited to classical drugs and should be completed with data of emerging new psychoactive substances (NPS). In this paper, K0 ‐values, LODs and drift times of 25 synthetic cannabinoids were evaluated. The data were added to existing databases of IMS which were then applied for fast screening of suspicious samples in prison.